EFEKTIFITAS METODE BLENDED LEARNING DALAM PROSES PEMBELAJARAN MAHASISWA KESEHATAN: A SCOOPING REVIEW - Rahimah, Hayatul; Mufdlilah, Mufdlilah; Hakimi, Moch. (Universitas Muhammadiyah Mataram, 2022)
Abstract: Currently, teaching in higher education is being intensively developed with a learning management system that records the learning behavior of students and teachers. Blended Learning is an integration of online learning methods and face-to-face learning. This scoping review aims to review the effectiveness of the blended learning method on the learning process of health students. Study identification through three databases (Pubmed, Proquest, and Sciencedirect), the search was limited to articles published in the last 10 years (2010-2020). The study was identified using the PRISMA flowchart, in identifying good quality articles the researcher conducted a critical appraisal with JBI tools. The findings in this review indicate that the blended learning method is effectively used as a learning method for health students. Effectiveness is seen from the increase in motivation and attitudes, knowledge, learning satisfaction, self-efficacy, and student competence after the application of the blended method. It can be concluded that the implementation of the blended learning method is effective in the learning process of health students, in addition to shifting the learning principle from being teacher-centered to being student-centered, blended learning also has the potential to increase the interaction between teachers and students, which leads to increased learning effectiveness.Abstrak: Saat ini, pengajaran di perguruan tinggi sedang gencar dikembangkan dengan sistem manajemen pembelajaran yang mencatat perilaku belajar siswa dan guru. Blended Learning atau metode pembelajaran campuran adalah integrasi dari metode pembelajaran online dan pembelajaran tatap muka. Scoping review ini bertujuan untuk mereview efektifitas metode blended learning terhadap proses pembelajaran mahasiswa kesehatan. Identifikasi studi melalui tiga database (Pubmed, Proquest dan Sciencedirect), pencarian dibatasi pada artikel yang diterbitkan 10 tahun terakhir (2010-2020). Studi diidentifikasi menggunakan diagram alur PRISMA, dalam mengidentifikasi artikel yang berkualitas baik peneliti melakukan critical appraisal dengan JBI tools. Temuan dalam review ini menunjukkan bahwa metode blended learning efektif digunakan sebagai metode pembelajaran mahasiswa kesehatan. Efektifitas dilihat dari peningkatan motivasi dan sikap, pengetahuan, kepuasan pembelajaran, efikasi diri, dan kompetensi mahasiswa setelah penerapan metode blended. Dapat disimpulkan bahwa implementasi metode blended learning efektif dalam proses pembelajaran mahasiswa kesehatan, selain dapat menggeser prinsip pembelajaran yang semula berpusat pada guru menjadi berpusat pada mahasiswa, blended learning juga berpotensi meningkatkan interaksi antara guru dan siswa, yang mana mengarah pada peningkatan efektifitas pembelajaran.